Fatal acidosis in a neonate with Pearson syndrome - Gürakan, Berkan; Özbek, Namık; Varan, Birgül; Demirhan, Beyhan (The Turkish Journal of Pediatrics, 1999)
We report a neonate who presented with hypotonia, hypoglycemia, and severe lactic acidosis. The patient's acidosis did not respond to bicarbonate replacement and dialysis. Postmortem liver samples revealed portal dilatation, fibrosis, canalicular proliferation, cholestasis, and hepatocellular hemosiderosis. Vacuolization of bone marrow precursors suggested a diagnosis of Pearson syndrome. A common mitochondrial DNA deletion of 4,978 bp was found. We emphasize that Pearson syndrome should be considered in neonates with lactic acidosis despite absence of anemia.
Keywords: lactic acidosis; neonate; Pearson syndrome